Statistical Study of Physicochemical Characteristicsof Wastewater in Odogunyan, Lagos, Nigeria - I. S. Akoteyon; O. Soladoye (E-Journal of Chemistry)
Physicochemical characteristics of wastewater samples collected from Odogunyan area was studied. Samples collected were designated (OWS1-OWS5) representing 5 sampling points and were analyzed for 14 parameters including; (pH, TSS, TDS, Cl, EC, BOD, COD, DO, Pb, Cr, Cu, Hg, Fe and Zinc) during the month of September 2009. The mean value obtained for total suspended solid & zinc were above FEPA stipulated tolerance limit in OWS2 & OWS5 whereas for zinc, it was above the stipulated limit in OWS2, OWS3 and OWS5. Cr was not detected except in two locations (i.e. OWS3 & OWS5). Although there is no FEPA’s limit for EC, the concentration obtained in OWS2 & OWS5 were relatively higher than the mean obtained. Mercury and Lead were not detected in all the samples.